2017
DOI: 10.1111/1440-1681.12841
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT modulates the rat mesenteric vasopressor outflow by 5‐HT1D sympatholytic receptors

Abstract: 5-hydroxytryptamine (5-HT) modulates noradrenergic activity in different cardiovascular territories, but its effect on the mesenteric vasopressor outflow has not yet been clarified. This study investigated the in vivo serotonergic influence, characterizing 5-HT receptors implicated, in sympathetic innervation of mesenteric vasculature. Wistar rats were anaesthetised and prepared for the in situ autoperfused rat mesentery, monitoring systemic blood pressure (SBP), heart rate (HR) and mesenteric perfusion pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Since pithed rats were used in this study, any influence of the central nervous system (which can produce baroreflex compensatory mechanisms in response to the effects produced by 5-HT and related agonists) can be excluded. Consequently, the nature of this experimental model helps explain why its resting values for both diastolic blood pressure and heart rate are much lower than those measured in anaesthetised (non-pithed) rats, where the neurogenic sympathetic tone is active [18,19,24,33].…”
Section: Systemic Haemodynamic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since pithed rats were used in this study, any influence of the central nervous system (which can produce baroreflex compensatory mechanisms in response to the effects produced by 5-HT and related agonists) can be excluded. Consequently, the nature of this experimental model helps explain why its resting values for both diastolic blood pressure and heart rate are much lower than those measured in anaesthetised (non-pithed) rats, where the neurogenic sympathetic tone is active [18,19,24,33].…”
Section: Systemic Haemodynamic Variablesmentioning
confidence: 99%
“…Within this context, 5-HT stands out as a neurohormone capable of regulating the sympathetic nervous system; certainly, the serotonergic system has been shown to modulate peripheral sympathetic neurotransmission at both the vascular and cardiac levels [13][14][15][16][17][18][19]. With respect to perivascular sympathetic innervation in pithed rats, our research team has already demonstrated that 5-HT induces sympatho-inhibition in the vasopressor discharge, mainly through activation of prejunctional 5-HT1A and 5-HT1D receptors [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The serotonergic system plays a pivotal function in cardiovascular homeostasis, both by directly regulating blood vessel contraction and dilation in different vascular beds such as mesentery, hindquarters, and kidneys [ 14 , 15 , 16 ], or by indirectly modulating the vegetative nervous system at the vascular and cardiac levels [ 17 , 18 , 19 , 20 ]. In this sense, 5-HT causes rat vascular sympatho-inhibition mainly by activation of 5-HT 1D receptors [ 18 , 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The serotonergic system plays a pivotal function in cardiovascular homeostasis, both by directly regulating blood vessel contraction and dilation in different vascular beds such as mesentery, hindquarters, and kidneys [ 14 , 15 , 16 ], or by indirectly modulating the vegetative nervous system at the vascular and cardiac levels [ 17 , 18 , 19 , 20 ]. In this sense, 5-HT causes rat vascular sympatho-inhibition mainly by activation of 5-HT 1D receptors [ 18 , 19 , 21 ]. However, experimental diabetes, as well as pharmacological 5-HT modulation by the antagonism of 5-HT 2 receptor, modify the serotonergic effect on the sympathetic discharge of rat vasculature [ 22 , 23 , 24 , 25 ], maintaining the main vascular sympatholytic effect of 5-HT.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, 5-HT stands out as a neurohormone capable of regulating the sympathetic nervous system; certainly, the serotonergic system has been shown to modulate peripheral sympathetic neurotransmission at both the vascular and cardiac levels 13 19 . With respect to perivascular sympathetic innervation in pithed rats, our research team has already demonstrated that 5-HT induces sympatho-inhibition in the vasopressor discharge, mainly through activation of prejunctional 5-HT 1A and 5-HT 1D receptors 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%